Analisis Daya Saing Teh Olahan (HS 210120) Indonesia di Pasar Global : Analysis of The Competitiveness of Processed Tea (HS 210120) from Indonesia in The Global Market - Mayda Rekha Azizah; Kralawi Sita; Sotya Tresna Anggita; Fadil Bagaskara; Arini Wahyu Utami (Jurnal Penelitian Teh dan Kina, 2026)
The tea plantation sector contributes the lowest amount of foreign exchange to the country compared to other plantation commodities. Processed tea products (HS 210120) have great potential due to their high added value. However, Indonesia's processed tea exports have fluctuated over the past ten years and are at their lowest level compared to the 15 major exporting countries. This study analyses the market structure, competitiveness, and trade specialisation index of processed tea in the global market using secondary data from 1989 to 2023 from UN Comtrade. The analysis methods include the Herfindahl-Hirschman Index (HHI), Revealed Comparative Advantage (RCA), Export Product Dynamic (EPD), Export Competitiveness Index (ECI), and Trade Specialisation Index. The results show that the processed tea market has an HHI concentration of 154.94 with a monopolistic competitive structure. RCA < 1 indicates low comparative competitiveness, but ECI > 1 indicates strong competitive competitiveness. The processed tea market is highly potential, so a development strategy is needed for Indonesia to compete sustainably in the global tea market